El coaching como herramienta de desarrollo personal en mujeres entre 25 y 30 años que viven en contextos de violencia intrafamiliar. - Maldonado Puente, Karina del Rocío (2016)
Coaching encourages personal development. It can help one redirect her path in life, even after having suffered prolonged domestic violence. Through a series of coaching workshops, women who had endured domestic abuse found they were finally able to confront the pain that had been inflicted upon them. Coaching provided these women with the tools necessary to truly recognize their personal worth. It has also been successful in teaching these women how to effectively navigate the problematic areas of their environments so that they can achieve the happiness they seek. When it comes to improving the overall mental health of the women who have been victims of domestic violence, it is of the utmost importance to highlight their strengths. It is often the case that victims of domestic abuse find it hard to identify their own personal strengths. In this way, the primary aim of coaching is to effectively help one solve day-to-day problems by simply giving one the resources she needs to enhance her personal performance. It has been shown that upon completion of a series of workshops, coaching improved the participants’ understanding of the issues at hand. In other words, the coaching group had become a center for support that helped its members to make important decisions. Importantly, this bidirectional encouragement prompted mutual positive change for all members of the group. The purpose of coaching is not to connect psychopathology with normalcy. Rather, it aims to work on both the positive and negative aspects of human behavior. In summary, coaching helps individuals generate concrete solutions that will help to improve their lives. Furthermore, it can teach individuals how to be functional in all environments while also enriching their life experiences and overall performance.